2007
DOI: 10.1029/2005jd007044
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal characteristics of the physicochemical properties of North Atlantic marine atmospheric aerosols

Abstract: The aerosol size distribution modal diameters show seasonal variations, 0.031 mm in winter and 0.049 mm in summer for the Aitken mode and 0.103 mm in winter and 0.177 mm in summer for the accumulation mode. The accumulation mode mass also showed a seasonal variation, minimum in winter and maximum in summer. A supermicron sized particle mode was found at 2 mm for all seasons showing 30% higher mass concentration during winter than summer resulting from higher wind speed conditions. Chemical analysis showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
227
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(260 citation statements)
references
References 40 publications
25
227
8
Order By: Relevance
“…The activity shows strong geographical and seasonal variations (Stramska, 2009). Measurements in Maze Head (Ireland) show organic aerosol concentration of several hundred ng m −3 connected with biologic activity in the ocean during spring to autumn (O'Dowd et al, 2004;Yoon et al, 2007). All three volcanoes studied here erupted in the biologically active part of the year.…”
Section: Carbonaceous Aerosol In Volcanic Cloudsmentioning
confidence: 99%
“…The activity shows strong geographical and seasonal variations (Stramska, 2009). Measurements in Maze Head (Ireland) show organic aerosol concentration of several hundred ng m −3 connected with biologic activity in the ocean during spring to autumn (O'Dowd et al, 2004;Yoon et al, 2007). All three volcanoes studied here erupted in the biologically active part of the year.…”
Section: Carbonaceous Aerosol In Volcanic Cloudsmentioning
confidence: 99%
“…The net accumulation sea-spray flux is based on Geever et al (2005) and is used as an organic-inorganic source function for the mixture of POC and sea salt aerosols. Recent measurements at the Mace Head station at the Atlantic coast of Ireland (O'Dowd et al, 2004;Yoon et al, 2007) have shown that OC contributes a considerable fraction to seaspray during periods of increased biological activity of the ocean. Further details are given in O' Dowd et al (2008).…”
Section: Model Set-upmentioning
confidence: 99%
“…Increase in sea-salt mass is primarily associated with increasing wind speeds with mass concentrations being measured up to 1000 mg m K3 at wind speeds of 15-20 m s K1 (Lewis & Schwartz 2004). Although mass loadings can be high, marine aerosol number concentrations are typically low, of the order of 300-600 cm K3 (O'Dowd et al 1997;Yoon et al 2007), of which up to 50-150 cm K3 can be sea-salt particles under high wind conditions (O'Dowd & Smith 1993;Kreidenweis et al 1998).…”
Section: Introductionmentioning
confidence: 99%